New species of terrestrial isopods (Isopoda: Oniscidea) from Sardinia - Taiti, Stefano; Argano, Roberto (Zootaxa, 2009)
Four new species of terrestrial isopods from Sardinia are described: Alpioniscus thanit sp. nov. (Trichoniscidae), Halophiloscia cristagalli sp. nov. (Halophilosciidae), Alloschizidium maymon sp. nov. and Alloschizidium magrinii sp. nov. (Armadillidiidae). Alpioniscus thanit and Alloschizidium magrinii were collected in endogean environments, Halophiloscia cristagalli on granitic beaches of small islands in the northern and western part of Sardinia, and Alloschizidium maymon from a cave. The diagnostic features and the affinities of the new species are discussed.